ANALISIS BIBLIOMETRIK MENGGUNAKAN VOSVIEWER: TREND RISET KETERAMPILAN BERPIKIR SISTEM DALAM PENDIDIKAN KIMIA - Amida, Nadia (ALOTROP, 2024)
This study examines the development of systems thinking skills research in chemistry education. The method used is bibliometric analysis with the help of the VOSViewer application. The research was conducted in 4 stages, namely: 1) collecting publication data using the Scopus database using the keyword "System thinking in chemistry education," 2) processing data using Microsoft Excel application, 3) bibliometric computational mapping analysis using the VOSViewer application, and 4) analyzing the results of computational mapping. Publication data are articles from 2014 to 2023. This research is limited to system thinking skills in chemistry education. The results of the initial findings were re-selected so that 67 publications that met the requirements for research were obtained. Based on the results of computational mapping, it was found that research over the past ten years has fluctuated with the most publications in 2019, a total of 31 publications. This study provides a comprehensive overview and holistic perspective of systems thinking skills in chemistry education and directions for future research by integrating the analysis results with relevant reviews.